MYCOMON-monitoring project of toxigenic fungi in food in years 1999 - 2001 - Ostry, Vladimir; Ruprich, Jiri; Skarkova, Jarmila; Prochazkova, Ivana; Kubatova, Alena (Mycotoxin research, 2002)
An occurrence of the toxigenic fungi producing aflatoxins and ochratoxin A in food was investigated in the study ("MYCOMON") in years 1999-2001. Twenty five commodities were purchased from retail in twelve collection places in the Czech Republic (300 food samples together). The presence of potentially toxigenic fungiAspergillus flavus was observed in 28% of the sampled food (black pepper, black tea, caraway seeds, fine flour, fruit tea, oat flakes) in the year 1999, in 17% of the sampled food (black pepper, black tea, caraway seeds, fine flour, fruit tea, oat flakes) in the year 2000 and in 18% of the sampled food (black pepper, black tea, caraway seeds, fine flour, fruit tea, oat flakes) in the year 2001.Aspergillus tamarii (aflatoxins producer) was found in black pepper samples (25%) in year 1999, in black pepper samples and black tea (25%) in year 2000 and in black pepper samples and black tea (21%) in year 2001.Aspergillus parasiticus andAspergillus nomius were not isolated.Aspergillus sectionNigri (potential producer of ochratoxin A) was detected in some food (black pepper, black tea, caraway seeds, fine flour, fruit tea, raisins, sweet red pepper).Penicillium verrucosum and Aspergillus ochraceus were not isolated from the tested food.